Socio-Legal Analysis of the Implementation of the 2023 Criminal Code in Society - Ady Ruswanto; Alia Trishanti; Bayu Winarko; Elyan Saputra; Syukron Abdul Kadir (Mandalika Institute, 2025)
The enactment of Law Number 1 of 2023 concerning the Criminal Code (KUHP 2023) marks a significant reform of Indonesia’s national criminal law, oriented toward humanitarian values, restorative justice, and the recognition of living law within society. Although previous studies have mainly examined the normative substance and political debates surrounding the new Criminal Code, limited attention has been given to its early social implementation and institutional readiness. This study aims to analyze the implementation of KUHP 2023 from a socio-legal perspective, particularly focusing on the level of understanding and readiness of both the public and law enforcement officials, as well as the sociological factors influencing its effectiveness. This research employs an empirical legal method with a qualitative approach, utilizing semi-structured interviews with 12 informants from law enforcement, academia, and society, supported by a literature review of regulations and scholarly sources. The findings indicate that law enforcement officials are relatively well-prepared at the structural level; however, the public still demonstrates a low and partial level of understanding of KUHP 2023. The primary inhibiting factors include a prison-centric culture, value pluralism, and potential uncertainty in the application of living law, while the supporting factors encompass the protection of privacy rights, recognition of customary law, and the adoption of a restorative justice approach. Analytically, these findings show that the effectiveness of criminal law reform depends not only on legislative change, but also on the interaction between legal norms, institutional capacity, and community legal culture. From a socio-legal perspective, the implementation of KUHP 2023 reflects a process of cultural transition that necessitates alignment between legal norms and the legal culture of society.